2017
DOI: 10.1371/journal.pone.0169720
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Ice Nucleation by Soufriere Hills Volcanic Ash Immersed in Water Droplets

Abstract: Fine particles of ash emitted during volcanic eruptions may sporadically influence cloud properties on a regional or global scale as well as influencing the dynamics of volcanic clouds and the subsequent dispersion of volcanic aerosol and gases. It has been shown that volcanic ash can trigger ice nucleation, but ash from relatively few volcanoes has been studied for its ice nucleating ability. In this study we quantify the efficiency with which ash from the Soufriere Hills volcano on Montserrat nucleates ice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(54 citation statements)
references
References 42 publications
5
48
1
Order By: Relevance
“…K-feldspars and quartz were found to be the two most efficient immersion INPs in mineral dust even though they were found in low weight percentages in samples [29]. In studies of volcanic ash, immersion INA has been either attributed to quartz [37], Na-feldspar [38], or K-feldspars [57]. These previous studies focus on the roles of particular minerals instead of bulk chemical composition, yet volcanic ash can contain many different elements present in an amorphous glass phase in addition to those existing in a crystallographic structure.…”
Section: Immersion-mode Ice Nucleation Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…K-feldspars and quartz were found to be the two most efficient immersion INPs in mineral dust even though they were found in low weight percentages in samples [29]. In studies of volcanic ash, immersion INA has been either attributed to quartz [37], Na-feldspar [38], or K-feldspars [57]. These previous studies focus on the roles of particular minerals instead of bulk chemical composition, yet volcanic ash can contain many different elements present in an amorphous glass phase in addition to those existing in a crystallographic structure.…”
Section: Immersion-mode Ice Nucleation Activitymentioning
confidence: 99%
“…However, there may be a bulk compositional effect at higher temperatures. Mechanical grinding of the grains may alter sites for ice formation and increase INA [31,37,38], and this may explain the deposition mode results, since all samples were mechanically milled to homogenize grain shape and size prior to the experiments. However, this apparent efficiency may simply result from all of the surface area available on which ice can nucleate (i.e., overseeding [8]), suggesting that all ash samples used here have similar values due to their similar surface areas.…”
Section: Deposition-mode Ice Nucleation Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Freely exposed feldspar are reported to be populated by lichens which can alter naturally occurring feldspar in an infinite number of ways (Smith, 1998). The surface properties (specific area, porosity, molecules on the surface) of freshly ground feldspar is therefore expected to be different from aged particles (Mangan et al, 2017). However, bulk composition and crystal structure can be assumed to be representative for natural feldspar.…”
Section: Chemical Composition 15mentioning
confidence: 99%
“…Despite the lower mass fraction of feldspars found in the airborne Saharan dust samples, Boose et al (2016) concluded that these could be relevant for atmospheric cloud glaciation at warmer temperatures (T > 250 K). Explosive volcanic eruptions can introduce large quantities of feldspar 25 particles into the atmosphere with a regional to global effect on cloud glaciation (Mangan et al, 2017). The analysis of ash particles that make up volcanic ash clouds showed that up to 70% can be feldspar (usually plagioclase feldspars, rarely sanidine) particles (Bayhurst et al, 1994,;Schumann et al, 2011).…”
mentioning
confidence: 99%